2019
DOI: 10.1021/acs.jpcb.9b04113
|View full text |Cite
|
Sign up to set email alerts
|

Structural Destabilization of Azurin by Imidazolium Chloride Ionic Liquids in Aqueous Solution

Abstract: Alkyl imidazolium chloride ionic liquids (ILs) have been used for numerous biochemical applications. Their hydrophobicity can be tuned by changing the alkyl chain length, and longer-chain ILs can form micelles in aqueous solution. We have investigated the effects of imidazolium chloride ILs on the structure and stability of azurin, which is a very stable Cu2+ redox protein with both α-helix and β-sheet domains. Temperature-dependent infrared (IR) and vibrational circular dichroism spectroscopy can provide seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 120 publications
1
12
0
Order By: Relevance
“…A brief summary of studies that have been published on azurin with ILs can be found in Table 4. [Cl] is stronger than the other ILs presented in this study, which were consisting of smaller alkyl chains and a decreased level of hydrophobicity [87]. It is important to note that at the concentrations tested, the [OMIM][Cl] has been shown to form micelles, These micelle structures likely impact the interactions with the protein, and can potentially form mixed structures with the protein.…”
Section: Effects Of Il On Azurinmentioning
confidence: 76%
See 4 more Smart Citations
“…A brief summary of studies that have been published on azurin with ILs can be found in Table 4. [Cl] is stronger than the other ILs presented in this study, which were consisting of smaller alkyl chains and a decreased level of hydrophobicity [87]. It is important to note that at the concentrations tested, the [OMIM][Cl] has been shown to form micelles, These micelle structures likely impact the interactions with the protein, and can potentially form mixed structures with the protein.…”
Section: Effects Of Il On Azurinmentioning
confidence: 76%
“…Standard Fourier transform IR (FTIR) can monitor secondary structures in the protein, while far-infrared spectroscopy (FIR) can be utilized to interrogate low-frequency vibrations, such as those in metal complexes [85,86]. These IR methods have been used to investigate the structure of numerous metalloproteins and peptides, including EndoIII, azurin, bovine serum albumin, and natural and designed peptides [86][87][88][89][90][91]. All of these pieces of information can together provide information regarding the stability of a protein's structure [92].…”
Section: Protein Folding/unfoldingmentioning
confidence: 99%
See 3 more Smart Citations